O Programa Primeira Escola da Prefeitura de Belo Horizonte: uma análise dos critérios de acesso às Unidades Municipais de EducaçãoInfantil - Laisa Kelly Vilanova (2010)
Our aim is to analyse how far the access criteria for the UMEI (Municipal Units for Children Education) contribute to the policy of Children Education in the city of Belo Horizonte by means of the Primeira Escola Programme, started in the year 2003, i.e., within the scope of Belo Horizontes attributions in regard to Children Education to analyse actions, strategies, and procedures adopted to face the relationship between the offer of public vacancies and the given demand. From this perspective, the criteria and the choices made for the UMEI locations to control the access and enrolment at schools, units, and municipal classes of Children Education have been analysed. The main question that mobilises us can be formulated as: What families are beingassisted by the new public units of Children Education in Belo Horizonte?The discussion presented in this study has been based on authors such as: Vieira (1998); Dalben et al (2002); Ferreira (2002); Silva (2002); Barbosa (2005) and Veiga (2005), amongst others. The concept of Children Education used in this article refers to the education of children ranging from the age of zero to five at public locations, out of their homes. In this sense, the methodological picture developed has been based on the use of quantitative and qualitative tools, including the bibliographic data collection, study of conceptual categories as social vulnerability, demand, social exclusion, among others; collection and analysis of statistical data, as well as semi-structured interviews with vice-directors of the UMEI selected for analysis, and managers from the citysSecretary of Education. Not willing to answer all questions arisen from the related analysis, some gaps related to the programme have been noticed, such as: the construction of Municipal Units forChildren Education away from the residences of the most vulnerable families, the non-checking of the data declared by the families at the time of enrolment at the institutions, the low salaries paid to teachers and the consequent high turnover among those professionals. Although the Programme is run through contradictions, one cannot flout that strategies and actions adopted by the Belo Horizonte Municipal Government represent an advance as to the policy of Children Education in the municipality. The increase in the offer of vacancies in ChildrenEducation by means of the Programme has contributed to reverse the trend of privatisation in Childhood assistance in the city, leading to the expansion of public assistance.